The Relation Ship Between Total Soil Microbes With N, P , K Nutrient Levels By Paddy Plant (Case Study In Ajamu Village, Panai Hulu District, Labuhanbatu Regency) - Kurnia Renaldy; Walida Hilwa; Khairul Rizal; Harahap FS (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The neglect of returning organic matter to the soil and the intensive use of chemical fertilizers inpaddy fields have caused the physical, chemical, and biological quality of the soil to decline. Such soilconditions cause the population of soil biota that plays a role in nitrogen fixation and phosphatesolubility to decrease. This study aims to determine the relationship between total microbes andnutrient levels of N, P, K in rice plants in Ajamu Village, Panai Hulu District, Labuhan Batu Regency.This research was conducted from December 2021 to January 2022. Sampling was carried out bytaking leaves and rhizosphere soil of rice plants at 5 zigzag sampling points in a rice field area.Parameters observed in this study were nutrient levels of N, P, K and total microbes. The analysis wascarried out using correlation and regression methods.